Examination ofmulti-layer silicon detector in measurementofelectron spectrumfor beta-decayof ⁹⁰SR- ⁹⁰Y - Bochek, G.L.; Golovash, A.S.; Kosinov, A.V.; Kotlyar, V.V.; Kulibaba, V.I.; Maslov, N.I.; Mazilov, A.A.; Naumov, S.V.; Ovchinnik, V.D. (Вопросы атомной науки и техники, 2005)
Brief survey of recent achievements in investigations of nuclear beta decays is given with some emphasis on superallowed 0⁺→ 0⁺ Fermi transitions between T=1 nuclear states. Progress in construction of a detecting system for registration of electrons and positrons in studies of beta transitions is discussed. The spectra of electrons emitted in decay of ⁹⁰Sr and ⁹⁰Y nuclides are measured with the help of double-sided silicon detector. The spectra obtained are compared with results of computer simulation. У доповіді коротко обговорюються досягнення в недавніх дослідженнях бета-розпадів атомних ядер. Основна увага приділяється понаддозволеним 0⁺→ 0⁺ переходам Фермі між ядерними станами з ізотопічим спіном, що дорівнює одиниці. Виконано виміри спектрів електронів, що випускаються в розпадах ядер ⁹⁰SR та ⁹⁰Y, за допомогою розроблювального двостороннього кремнієвого детектора. Отримані спектри порівнюються з результатами комп'ютерного моделювання. В докладе кратко обсуждаются достижения в недавних исследованиях бета-распадов атомных ядер. Основное внимание уделяется сверхразрешенным 0⁺→ 0⁺ переходам Ферми между ядерными состояниями с изоспином Т=1. Выполнены измерения спектра электронов, испускаемых в распадах ядер стронция-90 и иттрия-90, с помощью разрабатываемого двухстороннего кремниевого детектора. Полученные спектры сравниваются с результатами компьютерного моделирования.